Methane emission during on-site pre-storage of animal manure prior to anaerobic digestion at biogas plant: Effect of storage temperature and addition of food waste. (1st November 2018) - Feng, Lu; Ward, Alastair James; Moset, Veronica; Møller, Henrik Bjarne
Abstract: This study investigated the temperature dependency of CH4 emission from pre-storage of animal manure prior to anaerobic digestion at 15, 20, 25 and 30 °C using lab-scale anaerobic digesters. The manure was added and removed daily to simulate the pre-storage process at biogas plants. CH4 emission accounted for 1–46% of total CH4 potential from pig manure (PM) and 1–2% of that from cattle manure (CM) at the investigated temperatures, with significant increases above 25 °C. Addition of food waste (FW) reduced the CH4 emission when storage temperature was 20 °C or lower for PM and 25 °C or lower for CM due to volatile fatty acid accumulation and lower pH (<5.5) but emissions increased with higher storage temperatures. Graphical abstract: Highlights: The temperature dependency of CH4 emissions during storage of manure was evaluated. The effect of co-storage of manure with food waste was investigated. Food waste addition inhibited CH4 emission at lower temperatures. Emission at higher temperatures increased with addition of food waste.